The partisan : in the spy game, every move matters... - Worrall, Patrick (Union Square & Co., 2023)
"Summer 1961: The brutal Cold War between East and West is becoming ever more perilous. Two young prodigies from either side of the Iron Curtain, Yulia and Michael, meet at a chess tournament in London. They don't know it, but they're about to compete in the deadliest game ever played. Shadowing them is Greta, a ruthless Lithuanian resistance fighter who is hunting down some of the most dangerous men in the world. Men who are also on the radar of Vassily, perhaps the USSR's greatest spymaster. A man of cunning and influence, Vassily is Yulia's minder during her visit to the West, but even he could not foresee the consequences of her meeting Michael. When the world is accelerating towards an inevitable and catastrophic conflict, what can just four people do to prevent it?"--